FRI0044 RISK FACTORS FOR CORONARY ARTERY ATHEROSCLEROSIS IN PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Gerasimova, Helen; Popkova, Tatiana; Fomicheva, Olga; Krougly, Lev; Glukhova, Svetlana; Novikova, Diana
Abstract : Background: Rheumatoid arthritis (RA) is a systemic inflammatory disease leading to significant increase in cardiovascular morbidity and mortality. Development of coronary artery diseases (CAD) in RA patients (pts) is associated with the accumulation of traditional risk factors and immunological disorders. Coronary angiography (CAG) is the gold standard to identify coronary artery atherosclerosis (CAA). Objectives: To identify CAA predictors and determine CAA detection rates in RA pts with suspected CAD. Methods: Examination of 77 RA pts with suspected CAD, male/female 28/48, mean age 59 [53;64] years, with a long history of the disease (10[6;20] years), who were seropositive for IgM rheumatoid factor (RF) (82%) and anti-cyclic citrullinated peptide (ACCP) (58%), with moderate to high clinical disease activity DAS 28 4, 2[3, 2;5, 3]). CAG was performed in all pts. CAA risk factors in RA pts were identified by the multiple linear stepwise regression analysis. Results: Out of 77 RA pts CAA was detected in 52 (68%) (male/female 25/27 (group I)), while intact coronary arteries (CA) were found in 25 (32%) (male/female 3/22 (group II)) pts. Both groups were comparable in terms of age, disease duration and RA activity (DAS 28 score). Males prevailed in Group I: 48% vs 3% in Group II ( p <0, 05). Group I pts included more smokers than Group II (44% vs 8%, p<0, 05). Other traditional risk factors were equally represented in both groups: arterial hypertension - 87% and 84%, dyslipidemia - 75% and 64%, diabetes mellitus - 15% and 8%, physical inactivity - 58% and 42%, obesity - 29% and 28% pts in Groups I and II, respectively. Serum HDL cholesterol (HDL-C) concentrations were lower (1, 3[1, 0;1, 4] mmol/l) and triglyceride (1, 5[1, 1;2, 0]mmol/l) levels were higher in Group I vs Group II (1, 6[1, 2;1, 9] and (1, 2[0, 9;1, 5]mmol/l), p<0, 01). Concentration of total cholesterol and LDL-C were similar in pts from both Groups. Both Groups showed similar atherosclerotic plaques detection rates in carotid arteries (19/12%). Variety of administered drugs (disease-modifying antirheumatic drugs, biological drags and oral glucocorticoids) and therapeutic regimens were also comparable in Groups I and II. Multiple linear regression analysis indicates close association of CAA with pts' age (unstandardized coefficient B=0, 017, 95% confidence interval (95% CI) [0, 004-0, 030], p=0, 011), smoking (B=0, 246, 95% CI [0, 055-0, 437], p=0, 013), HDL-C (B=-0, 325, 95% CI [-0, 557-(-0, 095], p=0, 0073), atherosclerotic plaques in carotid arteries (B=0, 549, 95% CI [0, 120-0, 901], p=0, 003) and ACCP (B=0, 309, 95% CI [0, 028-0, 589], p=0, 03), coefficient of multiple determination (R 2 ) = 0, 6. Subsequent ROC analysis confirmed the diagnostic value of HDL-C and CAA in RA pts. HDL-C levels below 1, 32 mmol/l can be considered as a prognostic factor of CAA presence in RA pts with 68% sensitivity and 65%specificity (area under the curve is 0, 711; 95% CI 0, 580-0, 842; p = 0, 04). Conclusion: Male gender, low HDL-C levels, plaques in carotid arteries, and ACCP-positivity are associated with increased CAA risk in RA pts. Low HDL-C level can be considered as CAA predictor in RA pts. Disclosure of Interests: None declared